2018
DOI: 10.1105/tpc.18.00163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oryza sativa and Oryza brachyantha Genomes Reveals Selection-Driven Gene Escape from the Centromeric Regions

Abstract: Centromeres are dynamic chromosomal regions, and the genetic and epigenetic environment of the centromere is often regarded as oppressive to protein-coding genes. Here, we used comparative genomic and phylogenomic approaches to study the evolution of centromeres and centromere-linked genes in the genus We report a 12.4-Mb high-quality BAC-based pericentromeric assembly for, which diverged from cultivated rice () ∼15 million years ago. The synteny analyses reveal seven medium (>50 kb) pericentric inversions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 83 publications
2
17
0
Order By: Relevance
“…1c). This inversion has been reported previously to contain 404 genes (69), and it was also identified in O. brachyantha compared to indica assemblies (70). Another SV feature is genic hemizygosity, which can be estimated reasonably from SMRT reads (35).…”
Section: Svs Across Datasetssupporting
confidence: 62%
“…1c). This inversion has been reported previously to contain 404 genes (69), and it was also identified in O. brachyantha compared to indica assemblies (70). Another SV feature is genic hemizygosity, which can be estimated reasonably from SMRT reads (35).…”
Section: Svs Across Datasetssupporting
confidence: 62%
“…These findings suggested that NUPTs likely more accumulated in centromeric or pericentromeric regions in A. officinalis . Centromeric and pericentromeric regions are hotspots of organelle–nucleus DNA transfer [15, 39], because of the low gene density and high heterochromatin content of these regions [4346], which may provide a stable genomic environment for the integration of the organelle-derived DNA [6, 15]. However, Yoshida et al showed that NUPTs also accumulate in the distal regions of chromosomes [38].…”
Section: Discussionmentioning
confidence: 99%
“…NUPTs/NUMTs are usually distributed unevenly in the analyzed plant genomes [20,21,39]. NUPTs and NUMTs are more preferred to distribute in centromeric and pericentromeric regions [36,39], which have few genes and a high level of heterochromatin content [42][43][44]. Such regions may offer a stable genomic environment for the maintenance of the alien organelle-originated DNA [16,36].…”
Section: Organization and Distribution Patternsmentioning
confidence: 99%